Lipoic acid in secondary progressive MS: A randomized controlled pilot trial. Issue 5 (September 2017) - Spain, Rebecca; Powers, Katherine; Murchison, Charles; Heriza, Elizabeth; Winges, Kimberly; Yadav, Vijayshree; Cameron, Michelle; Kim, Ed; Horak, Fay; Simon, Jack; Bourdette, Dennis
Abstract : Objective: To determine whether lipoic acid (LA), an endogenously produced antioxidant, slowed the whole-brain atrophy rate and was safe in secondary progressive MS (SPMS). Methods: Patients with SPMS aged 40–70 years enrolled in a single center, 2-year, double-blind, randomized trial of daily oral 1, 200 mg LA vs placebo. Primary outcome was change in annualized percent change brain volume (PCBV). Secondary outcomes were changes in rates of atrophy of segmented brain, spinal cord, and retinal substructures, disability, quality of life, and safety. Intention-to-treat analysis used linear mixed models. Results: Participation occurred between May 2, 2011, and August 14, 2015. Study arms of LA (n = 27) and placebo (n = 24) were matched with mean age of 58.5 (SD 5.9) years, 61% women, mean disease duration of 29.6 (SD 9.5) years, and median Expanded Disability Status Score of 6.0 (interquartile range 1.75). After 2 years, the annualized PCBV was significantly less in the LA arm compared with placebo (−0.21 [standard error of the coefficient estimate (SEE) 0.14] vs −0.65 [SEE 0.10], 95% confidence interval [CI] 0.157–0.727, p = 0.002). Improved Timed 25-Foot Walk was almost but not significantly better in the LA than in the control group (−0.535 [SEE 0.358] vs 0.137 [SEE 0.247], 95% CI −1.37 to 0.03, p = 0.06). Significantly more gastrointestinal upset and fewer falls occurred in LA patients. Unexpected renal failure (n = 1) and glomerulonephritis (n = 1) occurred in the LA cohort. Compliance, measured by pill counts, was 87%. Conclusions: LA demonstrated a 68% reduction in annualized PCBV and suggested a clinical benefit in SPMS while maintaining favorable safety, tolerability, and compliance over 2 years. ClinicalTrials.gov identifier: NCT01188811. Classification of evidence: This study provides Class I evidence that for patients with SPMS, LA reduces the rate of brain atrophy.